Incorporating prior knowledge into Bayesian models for genetic evaluation in soybean breeding - Evangelista, Jeniffer Santana Pinto Coelho; Coelho, Igor Ferreira; Peixoto, Marco Antônio; Alves, Rodrigo Silva; Resende, Marcos Deon Vilela de; Silva, Felipe Lopes da; Bhering, Leonardo Lopes (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to compare the use of noninformative and informative priors in Bayesian models, as well as to evaluate the viability of including informative priors in the estimation of variance components and genetic values in soybean breeding programs. The used phenotypic data refer to the evaluation of 80 soybean genotypes in ten environments over three years. For each evaluated crop year, informative and noninformative priors were used, and the parameters were estimated using the Gibbs sampler algorithm. Parameter estimates from the previous crop year were used as prior information for the next evaluated crop year. The goodness-of-fit was calculated using the deviance information criterion (DIC). Selective accuracy showed the highest values for the models chosen through DIC for both crop years. However, the intervals of the highest posterior density are narrower for all models that adopted informative priors. Adding information into Bayesian inference does not always result in a better model fitting.